2021
DOI: 10.3390/cells10112949
|View full text |Cite
|
Sign up to set email alerts
|

Insights into COVID-19 Vaccine Development Based on Immunogenic Structural Proteins of SARS-CoV-2, Host Immune Responses, and Herd Immunity

Abstract: The first quarter of the 21st century has remarkably been characterized by a multitude of challenges confronting human society as a whole in terms of several outbreaks of infectious viral diseases, such as the 2003 severe acute respiratory syndrome (SARS), China; the 2009 influenza H1N1, Mexico; the 2012 Middle East respiratory syndrome (MERS), Saudi Arabia; and the ongoing coronavirus disease 19 (COVID-19), China. COVID-19, caused by SARS-CoV-2, reportedly broke out in December 2019, Wuhan, the capital of Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 165 publications
(156 reference statements)
0
27
0
Order By: Relevance
“…However, in certain cases, the activated immune response turns potentially pathological rather than protective, thereby causing dreadful and fatal health conditions like acute respiratory distress syndrome (ARDS), and eventual death. Therefore, the collective global fight against COVID-19, based on an array of effective interventions, including drug repurposing [ 128 , 129 ], antibody cocktail [ 130 , 131 ], vaccine [ 52 ], and stem cell-based therapy [ 132 ], are urgently required to millions of lives. This challenge is increasingly being compounded owing to the origin of various SARS-CoV-2 variants of concerns with enhanced intrinsic pathogenic properties [ 133 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in certain cases, the activated immune response turns potentially pathological rather than protective, thereby causing dreadful and fatal health conditions like acute respiratory distress syndrome (ARDS), and eventual death. Therefore, the collective global fight against COVID-19, based on an array of effective interventions, including drug repurposing [ 128 , 129 ], antibody cocktail [ 130 , 131 ], vaccine [ 52 ], and stem cell-based therapy [ 132 ], are urgently required to millions of lives. This challenge is increasingly being compounded owing to the origin of various SARS-CoV-2 variants of concerns with enhanced intrinsic pathogenic properties [ 133 ].…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 virion consists of a single RNA molecule, several accessory factors, and four categories of structural proteins: namely, spike (S), membrane (M), envelope (E), and nucleocapsid (N). These structural proteins intrinsically possess differential levels of immunogenicity [ 52 ], thereby eliciting a varied extent of immune responses with considerably different clinical consequences. Therefore, such structural proteins, especially glycosylated trimeric S protein [ 53 ] owing to its prominent immunogenic nature and crucial determinant of infection, are also the target for therapeutic intervention, apart from several host-derived cellular factors [ 54 ].…”
Section: Immune Responses To Sars-cov-2 Infectionmentioning
confidence: 99%
“…Given the critical need for pandemic control, efforts have been made to formulate high-performance vaccines with the maximum effective immune response and minimal side effects (28,29). So far, various prophylactic vaccines with different efficacy and safety have been approved for the COVID-19, depending on their structure and ability to elicit immune responses (30)(31)(32)(33). Multiple preclinical and clinical trial studies have been conducted or are underway to examine various aspects of COVID-19 vaccine platforms (15,17,34).…”
Section: Discussionmentioning
confidence: 99%
“…12,13 On the other hand, Chaudhary et al reported adverse reactions related to the use of vaccine excipients and/or adjuvants. 12 Previously, Xu et al studied the reproductive toxicity of adjuvants such as silver nanoparticles 14 in rabies virus vaccines and highlighted that their small size can allow crossing through biological barriers such as the blood-testis barrier, inducing cytotoxicity (inflammatory state and a decrease in mitochondrial function with the production of reactive oxygen species [ROS] and an increase in cellular apoptosis and/or a downregulation of gene expression, which could induce cellular apoptosis). Moreover, cytotoxicity has been associated with electrolyte imbalance between the intracellular membrane and the extracellular membrane, which leads to an alteration of metabolic activities.…”
Section: Xu Et Al Reported Structural Changes In Testicular Cells (Le...mentioning
confidence: 99%